2002
DOI: 10.1590/s1516-31802002000600005
|View full text |Cite
|
Sign up to set email alerts
|

Partial HELLP Syndrome: maternal and perinatal outcome

Abstract: We observed that aggressive procedures had been adopted for patients with PHS. These resulted in immediate interruption of pregnancy, with elevated cesarean rates and preterm delivery. Such decisions need to be reviewed, in order to reduce the cesarean rate and the incidence of preterm delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
3
14
1
2
Order By: Relevance
“…Rate of spinal anaesthesia were significantly less in HELLP syndrome (40.00%). 3 Results are comparable to the study.…”
Section: Methodssupporting
confidence: 74%
“…Rate of spinal anaesthesia were significantly less in HELLP syndrome (40.00%). 3 Results are comparable to the study.…”
Section: Methodssupporting
confidence: 74%
“…Batucatu et al found the incidence of HELLP to be 12.9%. 7 These were comparable to the present study while an Indian study by Chabbra S et al found it to be 23.58%. Study by Tandon A et al found incidence of HELLP 1.7% and partial HELLP 7.3%.…”
Section: Discussionsupporting
confidence: 91%
“…In the Botucatu's study on partial HELLP, preterm deliveries were 70.7% and IUGR was seen in 26.8% babies. 7 In the present study 3 (6.8%) babies in partial HELLP group had RDS while in HELLP one (2.9%) baby had RDS. Most common cause of morbidity was LBW and prematurity.…”
supporting
confidence: 43%
“…This is further supported by retrospective observations by Abbade et al, that there was a high rate of caesarean section rates and preterm delivery due to interruption of pregnancy with diagnosis of partial HELLP syndrome and such decisions needs review. 14 These findings were contradictory to later observations indicating that complete HELLP is associated with slightly high risk of maternal complications such as acute renal failure and DIC in comparison to partial HELLP with no difference in neonatal, long term and subsequent pregnancy outcomes. 15 Further support to these findings in an Asian study by Rakshit et al concluding partial HELLP has similar grave prognosis as complete HELLP.…”
Section: Discussionmentioning
confidence: 70%